The CASE Survey: Patient and Physician Perceptions Regarding Asthma Medication Use and Associated Oropharyngeal Symptoms - J Mark FitzGerald; Charles KN Chan; Martin C Holroyde; Louis-Philippe Boulet (Canadian Respiratory Journal)
BACKGROUND: Oropharyngeal (OP) symptoms are common in asthma patients using inhaled corticosteroids (ICSs) alone and in combination with a long-acting beta2-agonist (LABA). Patterns of medication use, level of asthma control and association with OP symptoms are not often reported in a nonstudy setting.